ANALYSIS OF HAEMATOLOGICAL AND HISTOPATHOLOGICAL MANIFESTATIONS IN GILLS AND MUSCLE OF FISH Channa punctatus (Bloch 1793) EXPOSED TO SYNTHETIC PYRETHROID DELTAMETHRIN - SRIVASTAVA, RAJESH KUMAR; SINGH, SHIVANGI; MISHRA, SHIVANGI; VERMA, PRAKRITI; TRIVEDI, SUNIL P.; RATN, ARUN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The aquatic ecosystem was especially faced with the threat of fish biodiversity loss due to indiscriminate use of pesticides in agriculture fields. The pesticides were entered into the aquatic regimes and affected their non-target animals like fishes. The present study aims the analysis of deleterious effects like haematological and histopathological alterations in type II synthetic pyrethroid deltamethrin exposed fish Channa punctatus. In experiment, the acclimatized fishes were exposed to sub-lethal concentration, 0.026 ppm (10% of 96 h-LC50 of deltamethrin) along with a control. The blood, gills and muscle tissues of fish were sampled out after 7, 14 and 28 days of exposure intervals. The significant (p < 0.05) decrement in red blood corpuscles count, hemoglobin and hematocrit, while, augmentation in white blood corpuscles count were found in deltamethrin exposed blood of fish. The noticeable histopathological abnormalities were observed in the gills and muscle of fish Channa punctatus. The control fish showed no histological alterations. In exposed fishes, the breakdown of the epithelial cell framework with numerous changes such as epithelial lifting (EL), congestion (C) and bulging (B) observed in fish gills. Also, the anomalies like fragmentation (FS) and bursting (Br) were found in the fish muscle. The findings illustrated the prominent haematological and histopathological perturbations in deltamethrin exposed blood, gills and muscle tissues of fish. These changes can be used as indicators for monitoring the aquatic pollution and helpful in the conservation of aquatic biodiversity including fishes.